Preparation, characterization and in vivo evaluation of nanoemulsions for the controlled delivery of the antiobesity agent N-oleoylethanolamine. (2014) - Wulff-Pérez, Miguel; Pavón, Francisco J; Martín-Rodríguez, Antonio; de Vicente, Juan; Alen, Francisco; de Fonseca, Fernando Rodríguez; Gálvez-Ruiz, María J; Serrano, Antonia
>Aims: N -oleoylethanolamine (OEA) is a lipid mediator that acts as a satiety factor. The main limiting factor for its administration is its poor water solubility. We designed and characterized new nanoemulsions as delivery system for hydrophobic compounds such as OEA.Materials & methods: The nanoemulsion components and preparation methods were selected in order to achieve the desired final properties. Then, we evaluated the in vivo properties of the nanoemulsions as drug-delivery systems testing the anorectic effects of OEA in rats after both intragastric and intraperitoneal administration. The in vivo toxicity of the nanoemulsions was evaluated after a 3-week treatment.Results: Nanoemulsions proved to be stable, nontoxic and had no effect on feeding behavior when administered without OEA. The effects of OEA were observable after its oral and parenteral administration with the nanoemulsions to 24-h fasted rats, finding a better efficacy compared with a vehicle containing Tween ® 20 (Sigma-Aldrich, MO, USA) after oral administration.Conclusion: These results support the efficacy of these nanoemulsions to deliver highly hydrophobic bioactive drugs. Original submitted 2 October 2013; Revised submitted 3 February 2014